An Integrative Review of the Quality and Outcomes of Diabetes Education Programs for Children and Adolescents. (October 2016) - Colson, Sébastien; Côté, José; Gentile, Stéphanie; Hamel, Valérie; Sapuppo, Cédric; Ramirez-Garcia, Pilar; Reynaud, Rachel; Lagouanelle-Simeoni, Marie-Claude
Purpose: The purpose of this study was twofold: (1) to describe the content of recent diabetes education programs and their outcomes in terms of glycemic control, disease management, and psychosocial criteria for children and adolescents with type 1 diabetes and (2) to gauge the match between these programs and the recommendations of the International Society for Pediatric and Adolescent Diabetes (ISPAD). Methods: The integrative review was carried out according to the Cochrane recommendations. Thirteen databases were searched for evaluations of education programs published from 2009 to 2014. Program characteristics and outcomes were described. Quality of studies was assessed, and program match with ISPAD recommendations was gauged. Results: Of 2528 studies found, 43 covering 36 education programs intended for youth with type 1 diabetes were retained for review. Nine of these centered on self-care competencies, 18 on psychosocial competencies, and 9 on both types of competency (mixed program). Programs varied widely in terms of organization, procedure, and content. Glycemic control was an indicator assessed in the majority of programs, but only half of these (for the most part, self-care programs) reported positive findings in this regard. Few programs seemed to affect psychosocial indicators. An online mixed program, which was the program that best met the ISPAD recommendations, proved to have an influence on glycemic control and several psychosocial criteria. Conclusions: Various avenues can be considered to improve participant engagement in education programs and to align these programs more closely with international recommendations. Further research is required to enhance knowledge in this field.